Customer satisfaction towards counter service: A case study at Road Transport Department Bukit Katil, Melaka / Noorazuan Ahmad and Muhamad Shafiq Md Koma - Ahmad, Noorazuan; Md Koma, Muhamad Shafiq (Faculty of Administrative Science and Policy Studies, 2013)
Counter service is frontline service which is important to the public organization and also private organization (Muhamad Sarji, 1992). Nowadays, counter service become one of the important service at government department to provide service to the public. It‟s important to government to always improve and monitor quality of customer service. This is because poor quality at counter service will make customer become dissatisfy and create negative image to the government agencies. Quality of counter service can be measure with SERVQUAL method by Parasuraman. Customer satisfaction can be defined as an overall customer attitude towards a service provider or an overall customer attitude towards a service provider or an emotional response to the difference between what customers expect and what they receive, as regards the achievement of some need, goal or wants (Hansemark & Albinson, 2004). In this study, there are several factors that can influence customer satisfaction towards counter service at government department. The factors are employees‟ performance, quality of counter service, waiting time and facilities and layout. So, the researchers‟ will study the factors in order to know the relationship between the factors and customer satisfaction. There are lots of suggestions from this study and might useful for future improvement.